N^2(n - 1) + 3(n - 1)
(n^2 + 3)(n - 1)
the answer is c
The answer is D. SIS idk how to do this
Ur welcome
Answer:
x=47
Step-by-step explanation:
Answer:
![5\times 0.76= 3.8](https://tex.z-dn.net/?f=5%5Ctimes%200.76%3D%203.8)
Step-by-step explanation:
Given: Marisa bought four bottles
Price of each bottle is $0.95.
Solving with the factors as given to find the total cost paid by Marisa.
Total cost= ![4\ bottles\times \$ 0.95= \$ 3.8](https://tex.z-dn.net/?f=4%5C%20bottles%5Ctimes%20%5C%24%200.95%3D%20%5C%24%203.8)
∴ Total cost paid by Marisa is $3.8.
As given to write an equation with the same product as the total cost but different factors.
∴ Lets assume the number of bottles bought by Marisa be "5" and cost of each bottle be "x"
We already find the total cost she paid is $3.8.
Now, writing an equation with different factors, as total cost remain same.
![5\times x= 3.8](https://tex.z-dn.net/?f=5%5Ctimes%20x%3D%203.8)
Dividing both side by 5
we get x= $ 0.76
∴ The required equation is ![5\times 0.76= 3.8](https://tex.z-dn.net/?f=5%5Ctimes%200.76%3D%203.8)
Just a moment while I review this